Management Practices and Holistic Development of Dance Troupe in Selected Secondary Schools - John Michael D. Aquino (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2022)
Management is a procedure of designing and sustaining an environment where everyone works together to attain the organization's goal. The study is a comparative analysis of the management practices of selected secondary public schools' dance troupe. This study is primarily anchored to the Skills Acquisition Theory (SAT). Specifically, the aims to identify the management practices and holistic development of the dance troupe members. The research study wants to determine the procedures in terms of rehearsals and training, community involvement, qualification of dancers, facilities, financial support, and the level of dancers' attributes in terms of attitude, discipline, and skills. The researcher also wants to determine if there is a significant relationship between the management practices and holistic development on the personal attributes of dance troupe members of the selected secondary public schools. Using a descriptive-quantitative methodology, a self-administered questionnaire was utilized in the survey of 172 dancers. The results revealed that dancers are well-disciplined and highly skilled. The management of the dance troupe struggles in terms of qualifications of the members, facilities, and financial support, which ultimately affect their preparation and training programs. Hence, there is a significant relationship between the management practices and holistic development of dance troupe members. The dance troupe's practices, skills, attitudes, and discipline have to maintain.